Role of Si segregation in the structural, mechanical, and compositional evolution of high-temperature oxidation resistant Cr-Si-B2±z thin films - Zauner, L.; Steiner, A.; Glechner, T.; Bahr, A.; Ott, Benedict; Hahn, R.; Wojcik, T.; Hunold, O.; Ramm, J.; Kolozsvári, S.; Polcik, P.; Felfer, Peter; et al. (Journal of Alloys and Compounds, 2023)
This work investigates the influence of Si-alloying up to 17 at.% on the structural, mechanical, and oxidation properties of magnetron sputtered CrB2±z-based thin films. Density-functional theory calculations combined with atom probe tomography reveal the preferred Si occupation of Cr-lattice sites and an effective solubility limit between 3 to 4 at.% in AlB2-structured solid solutions. The addition of Si results in refinement of the columnar morphology, accompanied by enhanced segregation of excess Si along grain boundaries. The microstructural separation leads to a decrease in both film hardness and Young's modulus from H ∼ 24 to 17 GPa and E ∼ 300 to 240 GPa, respectively, dominated by the inferior mechanical properties of the intergranular Si-rich regions. Dynamic thermogravimetry up to 1400 °C reveals a significant increase in oxidation onset temperature from 600 to 1100 °C above a Si content of 8 at.%. In-situ X-ray diffraction correlates the protective mechanism with thermally activated precipitation of Si from the Cr-Si-B2±z solid solution at 600 °C, enabling the formation of a stable, nanometer-sized SiO2-based scale. Moreover, high-resolution TEM analysis exposes the scale architecture after dynamic oxidation to 1200 °C (10 K/min heating rate) – consisting only of ∼20 nm amorphous SiO2 beneath ∼200 nm of nanocrystalline Cr2O3. In summary, the study provides detailed guidelines connecting the chemical composition with the respective thin film properties of high-temperature oxidation resistant Cr-Si-B2±z coatings.
CRIS-Team Scopus Importer:2023-02-24
Keywords: Borides; Mechanical properties; Oxidation resistance; Phase stability; Segregation; Si alloying; Thin films